2021
DOI: 10.1007/s10875-021-01051-1
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Hyper-IgE Syndrome—an Update and Unanswered Questions

Abstract: The hyper-IgE syndromes (HIES) are a heterogeneous group of inborn errors of immunity sharing manifestations including increased infection susceptibility, eczema, and raised serum IgE. Since the prototypical HIES description 55 years ago, areas of significant progress have included description of key disease-causing genes and differentiation into clinically distinct entities. The first two patients reported had what is now understood to be HIES from dominant-negative mutations in signal transduction and activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 138 publications
4
92
0
3
Order By: Relevance
“…The role of human IL-6, like that of IL-17A/F, has been progressively clarified by the study of IEI impairing its signaling ( Chen et al, 2021a ; Puel and Casanova, 2019 ). The description of dominant-negative mutations of STAT3 as the main cause of AD HIES ( Asano et al, 2021b ; Minegishi et al, 2007 ) revealed that impaired STAT3-dependent signaling downstream from several cytokines, including IL-6 ( Kane et al, 2014 ), caused the complex clinical and cellular phenotype observed in these patients characterized by severe early-onset atopic dermatitis, recurrent skin and sino-pulmonary bacterial infections, CMC, poor or delayed clinical and biological signs of inflammation, eosinophilia, high serum IgE levels, low levels of memory B and Th17 cells, and various nonhematopoietic features ( Tsilifis et al, 2021 ). Following this discovery, additional IEI associated with most, if not all of the clinical features observed in classical HIES, were reported, including AR deficiency of ZNF341, a transcription factor governing STAT3 expression and activity ( Beziat et al, 2018 ; Frey-Jakobs et al, 2018 ), and partial AR ( Chen et al, 2021b ; Schwerd et al, 2017 ; Shahin et al, 2019 ) or AD ( Beziat et al, 2020 ) deficiencies of GP130, the signaling receptor subunit common to all IL-6 family cytokines ( Rose-John, 2018 ), suggesting that impaired IL-6 immunity underlies many of the key immunological and clinical features of HIES.…”
Section: Il-6 and Staphylococcal Diseasementioning
confidence: 99%
“…The role of human IL-6, like that of IL-17A/F, has been progressively clarified by the study of IEI impairing its signaling ( Chen et al, 2021a ; Puel and Casanova, 2019 ). The description of dominant-negative mutations of STAT3 as the main cause of AD HIES ( Asano et al, 2021b ; Minegishi et al, 2007 ) revealed that impaired STAT3-dependent signaling downstream from several cytokines, including IL-6 ( Kane et al, 2014 ), caused the complex clinical and cellular phenotype observed in these patients characterized by severe early-onset atopic dermatitis, recurrent skin and sino-pulmonary bacterial infections, CMC, poor or delayed clinical and biological signs of inflammation, eosinophilia, high serum IgE levels, low levels of memory B and Th17 cells, and various nonhematopoietic features ( Tsilifis et al, 2021 ). Following this discovery, additional IEI associated with most, if not all of the clinical features observed in classical HIES, were reported, including AR deficiency of ZNF341, a transcription factor governing STAT3 expression and activity ( Beziat et al, 2018 ; Frey-Jakobs et al, 2018 ), and partial AR ( Chen et al, 2021b ; Schwerd et al, 2017 ; Shahin et al, 2019 ) or AD ( Beziat et al, 2020 ) deficiencies of GP130, the signaling receptor subunit common to all IL-6 family cytokines ( Rose-John, 2018 ), suggesting that impaired IL-6 immunity underlies many of the key immunological and clinical features of HIES.…”
Section: Il-6 and Staphylococcal Diseasementioning
confidence: 99%
“…In 1972, Buckley et al reported high serum IgE levels in patients with this condition, which was renamed HIES ( Buckley et al, 1972 ). These patients also have other clinical manifestations, including eosinophilia, low levels of inflammatory markers during infection, chronic mucocutaneous candidiasis (CMC), systemic allergic manifestations, and extrahematopoietic features, including facial dysmorphism, deciduous tooth retention, osteopenia, hyperextensibility, scoliosis, and vascular abnormalities ( Chandesris et al, 2012 ; Grimbacher et al, 1999 ; Tsilifis et al, 2021 ; Zhang et al, 2018b ) The manifestations of HIES display variable expressivity. The estimated frequency of HIES is between 1 per 100,000 to 1,000,000 at birth ( Ghaffari, 2018 ; Mogensen, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…We retrieved information concerning any history of BCG related infections (BCG-I). We selected diseases for which BCG is generally contraindicated (SCID, CID, CGD, MSMD), or diseases with reports of severe BCG infection (EDA-ID, STAT3 de ciency, STAT1 GOF) [3,12,13]. The results for all pooled patients, and for each disease are shown in gure 3.…”
Section: Resultsmentioning
confidence: 99%